Uniqueness and topological properties of number representation - Dovgoshey, O.; Martio, O.; Ryazanov, V.; Vuorinen, M. (Український математичний вісник, 2004)
Let b be a complex number with |b| > 1 and let D be a finite subset of the complex plane C such that 0 ∊ D and card D ≥ 2. A number z is representable by the system (D, b) if z = Σajbj , where aj ∊ D. We denote by F the set of numbers which are representable by (D, b) with M = −1. The set W consists of numbers that are (D, b) representable with aj = 0 for all negative j. Let F1 be a set of numbers in F that can be uniquely represented by (D, b). It is shown that: The set of all extreme points of F is a subset of F1. If 0 ∊ F1, then W is discrete and closed. If b ∊ {z : |z| > 1}\D′, where D′ is a finite or countable set associated with D and W is discrete and closed, then 0 ∊ F1. For a real number system (D, b), F is homeomorphic to the Cantor set C iff F\F1 is nowhere dense subset of R.